(untitled) (Comprehensive Journal of Science, 2025)
This study aims to measure the impact of money supply and exchange rate on Libya’s Gross Domestic Product (GDP) during the period from 2000 to 2024. The research relies on annual data obtained from the Central Bank of Libya and employs a descriptive analytical methodology. The findings reveal a statistically significant relationship between money supply, exchange rate, and GDP. Specifically, an increase in money supply contributes to GDP growth, with a coefficient of 0.160. Meanwhile, the exchange rate exhibits a stronger influence, with a coefficient of 5911.9. The study concludes that the exchange rate has a greater effect on GDP than the money supply. Accordingly, it recommends the adoption of balanced economic policies that support productive sectors and reduce dependence on imports.